PENGARUH KELOMPOK REFERENSI DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN DAN KEPUASAN KONSUMEN DEODORAN MEREK REXONA DI KALANGAN REMAJA DI KOTA PEKANBARU - Deni, Fujianto; Jushermi, Jushermi; Henni, Noviasari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine The Effect of Reference Group and Brand Image on Buying Decision and Customer Satisfaction Rexona brand deodorant among teenagers in Pekanbaru. The population in this study includes all consumers who buy and use Rexona in Pekanbaru City, while totally samples in this study is 100 people. The sampling technique in this study is Purposive Sampling, which is the selection of samples based on certain criteria. Data taken from respondents using questioners. The analytical method used in this research is path analysis using SPSS (Statistical Package for Social Science) aplication. The result show that : (1) Reference group influences the decision to buy deodorant rexona products among adolescents in Pekanbaru City (2) Brand image influences the decision to buy deodorant rexona products among teenagers in Pekanbaru City (3) Purchasing decisions affect consumer satisfaction of deodorant rexona products among adolescents in Pekanbaru City (4) Reference group influences consumer satisfaction of deodorant rexona products among adolescents in Pekanbaru City through the purchasing decision variable (4) Brand image affects consumer satisfaction of deodorant rexona products among adolescents in Pekanbaru City through the Purchasing Decision variable.Keywords : Refererence Group, Brand Image, Buying Decision and Customer Satisfaction